Światowa Organizacja Zdrowia i opieka medyczna sprawowana przez instytucje religijne w 30 lat po deklaracji w Ałma Ata - PAWŁOWSKI, ZBIGNIEW (Annales Missiologici Posnanienses, 2010)
Considerable changes, concerning the scope of the completion of the basic health care for all, which was offered originally in year 2000 are developing in very close relation to the missionary medical care centers. One of the most common issues is the idea of the basic health care for all. Another important question is linked to the role and future of medical centers run by religious institutions. Following matter is the necessary reorganization of the work of medical centers led by religious institutions. It is essential but have to be projected from the new global perspective. Finally going back to the main subject, the article presents the declaration published recently by the World Health Organization (WHO) on the collaboration with medical centers, guided by Faith-Based Organizations (FBO).